PENGARUH BENTUK IRISAN SINGKONG TERHADAP KARAKTERISTIK PENGERINGAN - Wendianing Putri Luketsi; Devi Urianty Miftahul Rohmah (Agroindustrial Technology Journal, 2019)
Cassava is one type of tuber that is very famous in Indonesia. Cassava in a state of fresh is easily damaged because it is very sensitive to the infestation of fungi and other microbes. Therefore it needs further processing, one of them is by drying. Cassava that has dried can be processed into cassava flour. In the drying process, the shape of the slices of cassava will affect the duration of drying, the quality and durability of cassava flour during storage. Therefore, the purpose of this study is to measure the yield of cassava and analyze the effect of cassava slices on drying characteristics. Before drying, cassava is cleaned and peeled. Peeled cassava is sliced in 3 slices, namely an upright circle with a thickness of 0,5 cm (S1), an oblique circle shape with a thickness of 0,5 cm (S2) and a circle shape of 5 cm thickness and then split upright into 8 or 4 parts with a thickness of 0,5 cm (S3). The data taken are peeled cassava, water content, dried cassava, rate of decrease in water content, and visual appearance of cassava drying. Based on the results of the study, the best cassava slices are sliced circle shape (S2) because of the accumulated data, the results obtained from S2 slices show maximum results.